Concordance between the National Healthcare Safety Network (NHSN) Surveillance Criteria and Clinical Pulmonary Infection Score (CPIS) Criteria for Diagnosis of Ventilator-associated Pneumonia (VAP) - Gunalan, Anitha (Indian J Crit Care Med, 2021)
Background: Ventilator-associated pneumonia (VAP) is one of the most common hospital-acquired infections among mechanically ventilated patients and the incidence rates are widely used as an index of quality of care given in an ICU. Since there is no gold standard method available to diagnose VAP, the incidence rate varies based on different criteria used for calculation. Therefore, we conducted a study to determine the concordance between the National Healthcare Safety Network (NHSN) surveillance criteria and clinical pulmonary infection score (CPIS) criteria for the diagnosis of VAP. Materials and methods: This was a prospective study that evaluated patients in the medical intensive care units (MICUs) of a tertiary care hospital, India, who were intubated for >48 hours between October 2018 and September 2019. All the patients (n = 273) were followed up daily and assessed using both CPIS and NHSN surveillance criteria for diagnosing VAP. Results: Of these 273 patients, 93 patients (34.1%) had VAP according to CPIS criteria as compared with 33 patients (12.1%) using the NHSN criteria. The corresponding rates of VAP were 39.59 vs 11.53 cases per 1,000 ventilator days, respectively. The agreement of the two sets of criteria was fairly good (kappa statistics, 0.42) Conclusion: The NHSN surveillance criteria have a lower sensitivity in detecting VAP cases and have to be modified to achieve better results. How to cite this article: Gunalan A, Sistla S, Sastry AS, Venkateswaran R. Concordance between the National Healthcare Safety Network (NHSN) Surveillance Criteria and Clinical Pulmonary Infection Score (CPIS) Criteria for Diagnosis of Ventilator-associated Pneumonia (VAP). Indian J Crit Care Med 2021;25(3):296–298.